Comprehensive rear surface passivation of superstrate Sb2Se3 solar cells via post-deposition selenium annealing treatments and the application of an electron blocking layer. (2nd August 2022) - Jeong, Giuk; Ji, Seunghwan; Choi, Jiwoon; Jung, Jihun; Shin, Byungha
Abstract : The passivation of defects associated with the Se deficiency on a rear surface of superstrate SbSe3 is acheived by post-deposition annealing treatment (PAT) under Se ambiance. The PAT greatly improves the device performance, mainly V oc and FF. Abstract : Sb2 Se3, a quasi-1D structured binary chalcogenide, has great potential as a solar cell light absorber owing to its anisotropic carrier transport and benign grain boundaries when the absorber layer is properly aligned along the [ hk 1] direction perpendicular to the substrate. A growth technique with a high deposition rate, such as vapor transport deposition, is preferred to form an [ hk 1]-oriented Sb2 Se3 film. However, the possible decomposition of Sb2 Se3 during cooling after the high-temperature deposition appears to result in Se deficiency, accompanied by the formation of deep-level donor-like defects, such as Se vacancies and Sb on Se antisite defects. Here, we present comprehensive passivation strategies for the rear interface of Sb2 Se3 solar cells in a superstrate configuration, namely a post-deposition annealing treatment (PAT) under Se, and the introduction of an electron-blocking layer between Sb2 Se3 and the rear metal contact. The PAT effectively passivated the defects associated with Se deficiency and greatly improved the open-circuit voltage and fill factor of Sb2 Se3 solar cells. With the further introduction of a poly( N, N -bis(4-butylphenyl)– N, N -bis(phenyl)benzidine) electron-blocking layer, the Sb2 Se3 solar cell achieved an efficiency of 7.0%.